Cellular and Network Mechanisms for Temporal Signal Propagation in a Cortical Network Model - He, Zonglu (Frontiers in Computational Neuroscience, 2019)
Effective (fast, reliable, and accurate) information propagation through multiple brain regions underlies cognitive processes. However, it remains unclear how neural circuits support the propagation, particularly over a background of irregular firing and response latency. Here, we propose a temporal coding model for the cellular and network mechanisms of the cortical propagation through the anatomical-functional integration across different scales of neural systems via dynamic, probabilistic, and statistical analyses. We hypothesize that synchronous spike events are a cortical population response to high-intensity thalamic input by which a high-density spike train is segregated into many low-density spike trains to avoid the lengthened latency caused by the high-intensity signal, thereby enhancing transfer speed. Moreover, cortical minicolumns prevent repeated activation of synchronous spiking events and facilitate transfer speed by parallel propagation via neurons with a column stereotypically interconnected in the vertical dimension, while columnar segregation avoids information loss in disassembly-parallel propagation. Under the Synchronous Spiking-Cortical Columns hypothesis, effective signal transfer in neural circuits relies on interneuron signal transfer with temporal-complete fidelity. We elicit a single-neuron encoder by modeling the membrane potential in response to stimulation as a resilience system in the nonlinear autoregressive integrated process derived by applying Newton's second law to stochastic resilience systems. A decoder is introduced to correct the response error of the encoder based on all-or-none law and backpropagation. Using the encoder-decoder as a signal propagator in interneurons, simulation studies are conducted where the input spike trains are generated by the right parietal 4 neuron and by a sound wave simulator, respectively. Statistical analysis and and simulations indicate that the encoder--decoder can effectively reproduce intracellular recordings from the right parietal 4 snail neuron and predict that interneuron transfer can achieve temporal-complete fidelity via regulations of ionic homeostasis and all-or-none law/backpropagation. Disfunctions of synchronous spiking and minicolumns may be the proximate cause of epilepsy or cognitive disease.